Calculation and Analysis of Temperature Distribution in Hot Rolling Strip - Kaixiang Peng (Institute of Advanced Engineering and Science, 2013)
Modern steel grades require constant and reproducible production conditions both in the hot strip mill and in the cooling section to achieve constant material properties along the entire strip length and from strip to strip. Calculation of the temperature in final rolling process always utilizes factors such as the work piece's inner organizational structure, plastic deformation, and it's variations of properties and so on, also as well as the physical parameters such as gauge, shape, etc. In this paper, a finite element model is constructed for the temperature field in a rolling process. The temperature field of strip steel is modeled with a 3-D finite element analysis (FEA) structure, simultaneously considering the distribution of the work roll temperature. Then the distribution of field is simulated numerically. From the model, the temperature contours can be obtained by analysis of the temperature distribution of contact area. At the same time, the distribution of temperature in any position at any time can be acquired. These efforts provide the reliable parameters for the later finishing temperature and shape control. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2845